Задача выбора режимов объединенной энергосистемы по активной мощности - Шарифов, Ф.А. (Теорія оптимальних рішень, 2007)
We consider the design minimum cost scheduling for choosing an active state of power systems that must be operated in a short time or for given time. We formulate the problem as finding a minimum nonlinear function with quadratic and linear type constrains.